2023
DOI: 10.1038/s41421-022-00513-z
|View full text |Cite
|
Sign up to set email alerts
|

A differentiation roadmap of murine placentation at single-cell resolution

Abstract: The placenta is one of the most important yet least understood organs. Due to the limitations of conventional research approaches, we are still far from a comprehensive understanding of mouse placentation, especially regarding the differentiation of trophoblast lineages at the early developmental stage. To decipher cell compositions and developmental processes, we systematically profile the single-cell transcriptomes of trophoblast cells from extraembryonic tissues (embryonic day 7.5 (E7.5) and E8.5) and place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…High-magnification photographs further showed that tdTomato was expressed in many clustered or scattered giant cells with characteristic large cytoplasms and nuclei (Bevilacqua & Abrahamsohn, 1988) (Figure 2g). P-TGCs are subdivided into primary P-TGCs and secondary P-TGCs (Jiang et al, 2023). In the placenta, the secondary P-TGCs and the spongiotrophoblast layer are together referred to as the JZ (El-Hashash et al, 2010) (Figure 2e).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-magnification photographs further showed that tdTomato was expressed in many clustered or scattered giant cells with characteristic large cytoplasms and nuclei (Bevilacqua & Abrahamsohn, 1988) (Figure 2g). P-TGCs are subdivided into primary P-TGCs and secondary P-TGCs (Jiang et al, 2023). In the placenta, the secondary P-TGCs and the spongiotrophoblast layer are together referred to as the JZ (El-Hashash et al, 2010) (Figure 2e).…”
Section: Resultsmentioning
confidence: 99%
“…To date, TGCs have been divided into four subtypes: spiral artery-associated TGCs (SpA-TGCs), canalassociated TGCs (C-TGCs), parietal TGC (P-TGCs), and sinusoidal TGC (S-TGCs), according to distinct functions and different locations within the placenta (Dunwoodie, 2009). P-TCGs can be further divided into primary P-TCGs differentiated from mural trophectoderm cells and secondary P-TCGs derived from the polar trophectoderm overlying the inner cell mass (ICM) (Jiang et al, 2023). During early gestation, P-TGCs mediate embryo implantation by regulating blastocyst attachment and invasion of the uterine epithelium (Dunwoodie, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…[27] To understand the impact of maternal androgen excess on placental development and cell type composition, we deconvoluted our bulk RNA-seq expression data using the cell type specific annotation from single-nuclei data at E10.5. [28] The placentas from PCOS-mice exhibited an increased proportion of decidua stromal cells but decreased proportion of trophoblast cells with a nearly 50% less trophoblast precursor cells compared to the control and flutamide-treatment (Fig. 4c-d, Supplementary Table 5).…”
Section: Androgen Exposure Disrupts Trophoblast Proliferation and Dif...mentioning
confidence: 89%
“…4d-e). The gene expression of Ddr2, encoding the discoidin domain receptor tyrosine kinase 2 and responsible for sensing the extracellular matrix (ECM) collagens, [28] was positively correlated with decidua stroma which was increased in the PCOS-mice placenta (Fig. 4e).…”
Section: Androgen Exposure Disrupts Trophoblast Proliferation and Dif...mentioning
confidence: 99%
“…The outer region of the ectoplacental cone differentiates to form more TGCs that envelop the whole fetus. 75,76 To comprehensively decipher this complex developmental process in mice, Jiang et al 77 performed single-cell RNA sequencing on trophoblast cells of extraembryonic tissues on embryonic days 7.5 and 8.5, and placental tissues from embryonic days 9.5 to 14.5. In that study, previously unreported progenitor cells and intermediate precursor cells were identified, and the lineage of differentiation trajectory was mapped during placentation in mice.…”
Section: In Micementioning
confidence: 99%